Efektifitas Chewing Gum dan Slow Deep Breathing Sebagai Strategi Adaptasi Terhadap Kecemasan Akademik: Suatu Literature Review dengan Pendekatan Model Adaptasi Roy - Cahyono, Ekhtya Dharma; Putri, Evita Muslima Isnanda; Nuryanti, Titik (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Academic anxiety can reduce concentration, impair working memory, and have a negative impact on academic performance. This study aims to synthesise the scientific evidence regarding the effectiveness of Chewing Gum Distraction (CGD) and Slow Deep Breathing (SDB) in reducing academic anxiety using the Roy Adaptation Model (RAM) framework. This study employed a literature review method with a systematic search across five international scientific databases Scopus, PubMed/MEDLINE, ScienceDirect, Wiley Online Library, and Google Scholar for publications from 2019 to 2025. The included articles were primary studies with a Randomised Controlled Trial (RCT), quasi-experimental, or experimental design investigating the CGD or SDB interventions on academic anxiety or stress among university students. A total of six articles met the inclusion criteria and were analysed thematically. The results of the review indicate that both interventions consistently reduced anxiety or stress levels significantly (p < 0.05). CGD operates through cognitive regulation by reducing rumination and modulating attention, whilst SDB operates through physiological regulation by increasing parasympathetic activity and autonomic stability. The combination of these two interventions has the potential to serve as an effective psychophysiological adaptation strategy for reducing students’ academic anxiety.